Optimizing Aqidah Akhlak Education as A Foundation for Character Building at The Primary School Level - Saputra, Moh. Aditya Hadi (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Aqidah akhlak education is basic education or religious foundation that must be instilled in children from an early age, one of the practical forms is through Islamic religious education subjects in elementary schools. Aqidah refers to faith, belief, and practice in Allah SWT. While Akhlak includes behaviours and habits that come from self-awareness in relationships with God, fellow humans, and the natural environment. Aqidah Akhlak learning focuses on aspects of intellectual intelligence and character building that must be applied seriously to form a person's character or characteristics. This study aims to assess the extent to which aqidah akhlak education affects the formation of diverse student characters in elementary schools. The method used in this study is the literature study method by analysing journals and previous research. The results showed that aqidah akhlak education plays an important role in shaping the character of elementary school students, accompanied by the role of teachers in learning, the role of the family as the first educational institution, and the community environment which has a major impact on student development at school